Perspectives for comprehensive biomechanical analyses in mogul skiing - Kurpiers, N.; McAlpine, P. R.; Kersting, U. G. (Research in Sports Medicine, 2009)
The purpose of this study was to examine the effects of using a force measurement device on riding technique in mogul skiing. A mock-up version of such a device was positioned between ski boot and binding. Data on three-dimensional kinematics and perception were collected for eight subjects skiing down a mogul course. Parameters analysed were knee angle, side and forward lean of the trunk and hip, and the path of the body's centre of mass. A perception questionnaire was used on selective aspects to assess the skiers' perception of the performances. Perception ratings showed no significant detrimental effects. All assessed components showed a trend of improvement from the first to last run, thus suggesting familiarisation was achieved. Kinematic analysis revealed that no significant alterations occurred. In conclusion, it is intended to utilise a functional force plate similar to the one presented by Kiefmann et al. (2006) for future studies in freestyle skiing.